Development of a medication review intervention by seconding a hospital pharmacist to primary care - Sara Sommer Holst; Johanne Mølby Hansen; Susanne Kaae; Charlotte Vermehren (Exploratory Research in Clinical and Social Pharmacy)
Background: Medication reviews (MRs) are a well-described initiative that improves health outcomes for polypharmacy patients. However, there is limited knowledge about the performance of medication reviews carried out in general practice especially under the leadership of hospital clinical pharmacists. When developing complex interventions, such as MRs, it is essential to describe the development process to ensure transparency and avoid research waste. Objective: Thus, this study aimed to describe the steps of developing a new MR intervention targeting general practice to ensure transparency and transferability. Methods: A stepwise approach inspired by the Medical Research Council framework was utilised in the process, covering two of the phases, i.e., development and feasibility, divided into four steps: 1) intervention drafting by a literature search, 2) expert opinion, 3) pilot testing in general practice clinics, and 4) evaluation of quantitative MR data. Results: Based on the results from the first three steps, four main themes which influenced the success of the MR intervention were identified: general practitioner resources, patient involvement, implementation difficulties and interdisciplinarity. These themes guided the pilot evaluation in step four. Conclusion: A new feasible, complex MR intervention utilising clinical pharmacists in general practice involving hospital clinical pharmacists in a real-life setting was developed.